The new carbon economy - Newell, Peter (Peter John); Boykoff, Maxwell T.; Boyd, Emily (John Wiley & Sons, 2012)
The New Carbon Economy provides a critical understanding of the carbon economy. It offers key insights into the constitution, governance and effects of the carbon economy, across a variety of geographical settings. Examines different dimensions of the carbon economy from a range of disciplinary angles in a diversity of settingsProvides ways for researchers to subject claims of newness and uniqueness to critical scrutinyHistoricizes claims of the 'newness' of the carbon economyCovers a range of geographical settings including Europe, the US and Central America.